Reduced Infectivity in Cattle for an Outer Membrane Protein Mutant of Anaplasma marginale - Crosby, Francy L. (Appl Environ Microbiol, 2015)
Anaplasma marginale is the causative agent of anaplasmosis in cattle. Transposon mutagenesis of this pathogen using the Himar1 system resulted in the isolation of an omp10 operon insertional mutant referred to as the omp10::himar1 mutant. The work presented here evaluated if this mutant had morphological and/or growth rate defects compared to wild-type A. marginale. Results showed that the morphology, developmental cycle, and growth in tick and mammalian cell cultures are similar for the mutant and the wild type. Tick transmission experiments established that tick infection levels with the mutant were similar to those with wild-type A. marginale and that infected ticks successfully infected cattle. However, this mutant exhibited reduced infectivity and growth in cattle. The possibility of transforming A. marginale by transposon mutagenesis coupled with in vitro and in vivo assessment of altered phenotypes can aid in the identification of genes associated with virulence. The isolation of deliberately attenuated organisms that can be evaluated in their natural biological system is an important advance for the rational design of vaccines against this species.